Forty years in the wilderness: John Sadler of the Sadler Partbooks - Range, M; Craig-McFeely, J (Oxford University Press, 2020)
The identification of the Tudor partbooks Oxford, Bodleian Library, Mss. Mus. e. 1–5 and Ms. Tenbury 1486, and the privately owned Willmott partbook with John Sadler, a priest and schoolmaster active in rural Northamptonshire between 1548 and the early 1590s, has sat uneasily. This is because the John Sadler associated with these books is actually someone quite different: in the first set he entered in the books what has previously been described as a simple monogram of his name, but which is in fact a ‘merchant mark’ identifying him unambiguously as a Norwich merchant. The article discusses the evidence for his identification and the new context for the books. Their relocation invites a new reading and interpretation of their contents, such as their significance as a source of information about the Norwich composer Thomas Morley. The link with the Elizabethan merchant world brings into focus the rather neglected topic of early modern merchants and their involvement with music.